Regulating Dendrite‐Free Zinc Deposition by Red Phosphorous‐Derived Artificial Protective Layer for Zinc Metal Batteries. Issue 18 (24th April 2022) - Wang, Tian; Xi, Qiao; Li, Yifan; Fu, Hao; Hua, Yongbin; Shankar, Edugulla Girija; Kakarla, Ashok Kumar; Yu, Jae Su
Abstract: Rational architecture design of the artificial protective layer on the zinc (Zn) anode surface is a promising strategy to achieve uniform Zn deposition and inhibit the uncontrolled growth of Zn dendrites. Herein, a red phosphorous‐derived artificial protective layer combined with a conductive N‐doped carbon framework is designed to achieve dendrite‐free Zn deposition. The Zn–phosphorus (ZnP) solid solution alloy artificial protective layer is formed during Zn plating. Meanwhile, the dynamic evolution mechanism of the ZnP on the Zn anode is successfully revealed. The concentration gradient of the electrolyte on the electrode surface can be redistributed by this protective layer, thereby achieving a uniform Zn‐ion flux. The fabricated Zn symmetrical battery delivers a dendrite‐free plating/stripping for 1100 h at the current density of 2.0 mA cm –2 . Furthermore, aqueous Zn//MnO2 full cell exhibits a reversible capacity of 200 mAh g –1 after 350 cycles at 1.0 A g –1 . This study suggests an effective solution for the suppression of Zn dendrites in Zn metal batteries, which is expected to provide a deep insight into the design of high‐performance rechargeable aqueous Zn‐ion batteries. Abstract : An artificial protective layer based on zinc‐phosphorus (ZnP) alloying reaction is designed to regulate the deposition behavior of Zn ions. The synergistic effect of the ZnP alloy artificial protective layer and carbon framework enables a uniform electric field strength distribution and a homogeneous Zn‐ion flux on the electrode surface, which results in the dendrite‐free Zn plating/stripping.